2020
DOI: 10.4149/bll_2020_008
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 expression is correlated with pathological stage in luminal subtypes of breast carcinoma

Abstract: AIM: STATs and HIFs in human solid tumors play an important role in mechanisms of tumor growth. The aim of this study was to determine the prognostic role of STATs and HIFs in breast cancers. METHODS: Twenty-four breast carcinoma cases who underwent mastectomy and axillary dissection were included into the study. The presence of STATs and HIFs in 24 breast cancer cases was evaluated immunohistochemically. We evaluated the differences in tumor grade, diameter, limits, intratumor desmoplasia, infl ammatory infi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The result suggested that compared to normal tissues, the expression levels of STAT1 and STAT2 were higher in BRCA tissues, while those of STAT3, STAT4, STAT5A, and STAT5B were lower. We also found that STAT3 was significantly associated with the pathological stage of BRCA, which indicates that STAT3 might play an important role in the occurrence and development of BRCA (32,33). More importantly, through mutual verification by several database tools, we observed that BRCA patients with a high transcriptional level of STAT4 were apparently related with long OS.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The result suggested that compared to normal tissues, the expression levels of STAT1 and STAT2 were higher in BRCA tissues, while those of STAT3, STAT4, STAT5A, and STAT5B were lower. We also found that STAT3 was significantly associated with the pathological stage of BRCA, which indicates that STAT3 might play an important role in the occurrence and development of BRCA (32,33). More importantly, through mutual verification by several database tools, we observed that BRCA patients with a high transcriptional level of STAT4 were apparently related with long OS.…”
Section: Discussionsupporting
confidence: 51%
“…There is some evidence that STAT family proteins, particularly STAT3, play a key role in the selective induction and maintenance of an oncogenic inflammatory microenvironment, both at the onset of malignant transformation and during cancer progression (42). Furthermore, STAT3 has been shown to be particularly active in BRCA, where it promotes cancer progression by stimulating cell proliferation, increasing angiogenesis, influencing escape to the immune system, and providing resistance to apoptosis (33,43). In our research, STAT3 expression was related to the pathological stage of BRCA, which could perhaps be explained by the mechanism described above.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates tumor trophoblastic angiogenesis and the immune response of interstitial cells [ 7 ]. Research has found that the expression of STAT3 is abnormally high and persistently activated in many human solid tumors and hematoma cells [ 8 ], such as thyroid carcinoma [ 9 ], liver carcinoma [ 10 ], breast carcinoma [ 11 ] and pancreatic carcinoma [ 12 ]. Inhibiting the activation of STAT3 using knockout systems or inhibitors can significantly repress tumor progression, emphasizing the importance of blocking the STAT3 signal cascade in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical approaches in humans have found increased levels of nuclear‐localized STAT3 in malignant BCs when compared with normal tissues (Watson, 2001). A recent study has identified that STAT3 expression was found to have a significantly higher correlation with luminal breast cancer (Eroglu et al, 2020). Hence, according to these data and because of its implication in cancer development and progression, Signal transducer and activator of transcription protein 3 ( STAT3 ), has been recognized as a type of oncogene (Bromberg et al, 1999).…”
Section: Introductionmentioning
confidence: 99%